2021
DOI: 10.3390/medicina57060571
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Survey for Plastic Surgery Malpractice Claims in Rome, Italy

Abstract: (1) Introduction: Medical malpractice claims against both health institutions and physicians are a crucial topic in Italy, as well as in other countries, particularly regarding civil proceedings. Our study reports an analysis of all of the malpractice judgments concerning plastic surgery decided in the Civil Court of Rome between 2012 and 2016. (2) Methods: the database of the Observatory Project on Medical Responsibility (ORMe) was analyzed, which collects all of the judgments of the Civil Court of Rome, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…According to an example reported in a paper published in 2003 by an eminent scientific journal, the observance of hand washing in hospitals ranges from 16% to 81% [ 15 ] a wide variability affecting both patients’ health and, as discussed above, judgment outcomes The data reported show that the surgical area is the most involved with 54% of cases concerning only three branches: orthopedics, cardiac surgery, and general surgery. These data, substantially in line with what is reported in the scientific literature [ 16 , 17 , 18 ], confirms the data relating to SSIs’ incidence, representing the subject matter of the litigations in 93 out of 140 cases (including both fatal and non-fatal injuries) for a total of EUR 8,782,343.41 of compensation paid. With reference to the health costs deriving from SSIs, it is estimated that about 60% of cases might be prevented by complying with the existing guidelines, that patients were exposed to a risk of death 2 to 11 times higher, and that over 70% of these deaths were specifically attributable to SSIs.…”
Section: Discussionsupporting
confidence: 90%
“…According to an example reported in a paper published in 2003 by an eminent scientific journal, the observance of hand washing in hospitals ranges from 16% to 81% [ 15 ] a wide variability affecting both patients’ health and, as discussed above, judgment outcomes The data reported show that the surgical area is the most involved with 54% of cases concerning only three branches: orthopedics, cardiac surgery, and general surgery. These data, substantially in line with what is reported in the scientific literature [ 16 , 17 , 18 ], confirms the data relating to SSIs’ incidence, representing the subject matter of the litigations in 93 out of 140 cases (including both fatal and non-fatal injuries) for a total of EUR 8,782,343.41 of compensation paid. With reference to the health costs deriving from SSIs, it is estimated that about 60% of cases might be prevented by complying with the existing guidelines, that patients were exposed to a risk of death 2 to 11 times higher, and that over 70% of these deaths were specifically attributable to SSIs.…”
Section: Discussionsupporting
confidence: 90%
“…Law n.24 is still being implemented, and several years are needed to assess the effects on patient safety culture and litigation prevention to achieve the stated goals by monitoring adverse events and reducing medical liability and the costs of the healthcare system [ 29 , 30 ]. Several studies suggested that educational programs and patient safety culture improvement lead to a reduction in the number of adverse events and greater patient and HCW safety perspectives in healthcare facilities [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For plastic surgery, studies show that most complaints are related to patients' dissatisfaction with the results of cosmetic interventions [27,46]. In this regard, some authors suggest that complaints arise due to poor and unclear information about the expectations that patients should have after cosmetic interventions [27,47]. In addition, studies that targeted only plastic surgeons showed a 2.5 times higher risk among doctors who focus on cosmetic interventions in their practice, compared with others [27].…”
Section: Discussionmentioning
confidence: 99%